Efficiency of Dimethyl Sulphoxide and Ethylene Glycol on Subsequent Development of Vitrified Awassi Sheep Embryos - Omar R Mardenli; MS Mohammad; HA Hassooni (Indonesian Center for Animal Research and Development (ICARD), 2020)
The use of cryoprotectants in vitrification would reduce the critical damages to the embryos, thus increase the survival rates. This research was conducted in the laboratory of reproductive biotechnology at the faculty of Agriculture of Aleppo University. The study aimed to evaluate the viability and survivability of early Syrian Awassi embryos under the influence of dimethyl sulphoxide (DMSO) and ethylene glycol (EG) following vitrification. Embryos were vitrified in three solutions of cryoprotectants (A: DMSO (3 ml), B: EG (3 ml), and C which was composed of a combination of DMSO (1.5 ml) and EG (1.5 ml)). After thawing, embryos that had been vitrified in C solution achieved the highest rates of cleavage (P< 0.01) comparing with A and B solutions for 2-16 cell stage (50.00% Vs 30.77% and 36.36%), morula (9.00% Vs 44.44% and 40.00%) and blastocyst stage embryos (92.86% Vs 58.33% and 50.00%) respectively. Down to the hatching blastocyst stage, 2-16 cell stage vitrified embryos in C solution achieved an encouraging rate comparing with A and B solutions (39.20% Vs23.08% and 22.73% respectively). The rates of arrested embryos decreased significantly (P< 0.05) after thawing across the three solutions especially the morula and blastocyst stage (0.00 and 3.70% respectively) (C solution). No significant differences were observed in the three types of embryos across all stages and solutions despite the large range among these rates. Given the apparent benefit of the participatory effect of cytoprotectants, it is advised to use a mixture of DMSO and EG (1:1) in vitrification of ovine embryos.